2010
DOI: 10.1113/expphysiol.2010.053538
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine receptor inhibition with theophylline attenuates the skin blood flow response to local heating in humans

Abstract: Mechanisms underlying the robust cutaneous vasodilatation in response to local heating of human skin remain unresolved. Adenosine receptor activation has been shown to induce vasodilatation via nitric oxide, and a substantial portion of the plateau phase to local heating of human skin has been shown to be dependent on nitric oxide. The purpose of this study was to investigate a potential role for adenosine receptor activation in cutaneous thermal hyperaemia in humans. Six subjects were equipped with four micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 39 publications
2
64
1
Order By: Relevance
“…Although occurring at larger doses, Fieger & Wong (2010) mentioned a 'nonspecific vasodilatation' following the administration of theophylline. No significant differences were observed in the subsequent relative decreases of CVC during the first cooling period.…”
Section: Adenosine and Cutaneous Vasoconstrictionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although occurring at larger doses, Fieger & Wong (2010) mentioned a 'nonspecific vasodilatation' following the administration of theophylline. No significant differences were observed in the subsequent relative decreases of CVC during the first cooling period.…”
Section: Adenosine and Cutaneous Vasoconstrictionmentioning
confidence: 99%
“…The theophylline concentration used was based on that reported by Fieger & Wong (2010, 2012, while that for L-NAME was chosen based on previous studies (Minson et al 2001;Fieger & Wong, 2010). Infusions were maintained for a 45 min period to ensure the establishment of each blockade (Minson et al 2001;Fieger & Wong, 2010).…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The data of these researchers suggested that adenosine receptor activation directly contributes to cutaneous thermal hyperemia and that a portion of the NO response may be explained by adenosine receptor activation. However, a substantial portion of the NO response is independent of adenosine receptor activation [77]. Additionally, neurokinin-1 receptors contribute to both the axon reflex component and the secondary plateau phase of cutaneous thermal hyperemia [78].…”
Section: Retrodialysis In Experimental Human Studiesmentioning
confidence: 99%
“…Fieger and Wong [77] investigated the potential role of adenosine receptor activation in cutaneous thermal hyperemia because adenosine receptor activation induces vasodilatation via NO and because a substantial portion of the plateau phase of local heating of human skin depends on NO. The data of these researchers suggested that adenosine receptor activation directly contributes to cutaneous thermal hyperemia and that a portion of the NO response may be explained by adenosine receptor activation.…”
Section: Retrodialysis In Experimental Human Studiesmentioning
confidence: 99%